Reply to the letter to the editor by Viroj Wiwanitkit concerning: 'Is neutrophil-lymphocyte ratio associated with the severity of allergic rhinitis in children?' - Doğru, Mahmut; Evcimik, Muhammed Fatih; Cirik, Ahmet Adnan (Springer, 2016)
We appreciate to receive these constructive and valuable comments regarding our article entitled ‘‘Is neutrophil– lymphocyte ratio associated with the severity of allergic rhinitis in children?’’ [1]. As mentioned by Wiwanitkit, it is more feasible to analyze the blood samples on the same analyzer [2]. However, the results were obtained on two separate analyzers, as the analyzer used to perform complete blood count in our hospital was changed after August 2013. When the blood samples were re-analyzed in terms of the analyzers, neutrophil–lymphocyte ratio (NLR) values in the AR group were found to be higher before August 2013 and the difference was not statistically significant (p = 0.179).
WOS: 000382945900079
PubMed ID: 27473294
Keywords: Neutrophil–Lymphocyte; Atio Associated; Severity of Allergic